Evaluación de diferentes niveles de harina de maracuyá (Pasiflora edulis) en la cría y acabado de pollos broiler - Veloz Bazantes, Juan Patricio (2019)
Different levels of passion fruit flour (Pasiflora edulis) were evaluated in the breeding and finishing of broiler chickens, proposing the following general objective: Evaluate different levels of passion fruit flour in the broiler breeding and finishing of Broiler chickens and the specific objectives, 1. - Establish the best level of passion fruit flour in the broiler breeding and finishing. 2. - Determine the economic analysis in the benefit-cost ratio. This investigation was made in the city of Guaranda Province of Bolívar with an altitude of 2800msnm having an average annual humidity of 75% and a maximum temperature of 24 ° C and a minimum of 10 ° C. Among the most important livestock activities in Ecuador is poultry farming, which is equivalent to approximately 13% of agricultural GDP in 2012, with a per capita consumption of chicken meat of 32Kg / year. The fruit of maracuyá is produced in its totality at national level and like the objective of its production they are the drinks and extracts, most of the fruit remains without using; Thus, this research was carried out in which the cascara of this fruit is processed to obtain the passion fruit flour and incorporated into the diet of the birds, for which this passion fruit flour was used in different levels of (10%) (12%) (14%) and also 192 chickens distributed in 4 treatments and 4 repetitions with 12 chicks per repetition, in which a Design of Completely Random Blocks (DBCA) with the same repetition was used. The treatments that were submitted to the investigation with passion fruit flour as a nutritional supplement showed a significant difference in the variables of Weight (P), Gain of that (GP), Food conversion (CA), Hematological Analysis. Once the statistical analyzes were carried out, it was obtained that T4 (passion fruit flour at 14%) obtained a better average weight of 3322.9 g, a weight gain of 3278.3 g and a feed conversion of 0.99%. In addition, a 28-day analysis was performed in which the T4 obtained the values within the hematological constants of the chicken, in contrast to the T1 that had a decrease in red blood cells because the passion fruit flour has a large amount of iron and another analysis at 42 days, these values being within the hematological constants of the chicken.